Consumer Acceptance of a Pay-As-You-Throw (PAYT) System for Food Waste Management in Baku, Azerbaijan - Alizadeh, Faraz (My University, 2026)
The paper focuses on psychological and socio-technical factors that impact consumer adoption of a PAYT system in managing food waste in Baku, Azerbaijan. An extended Theory of Planned Behavior (TPB) model was applied as the theoretical base for the analysis. A structured questionnaire including 25 questions on a 7-point Likert scale was developed for 53 city dwellers. Multiple regression analysis, supplementary single-extension analyses, and group comparisons with the aid of Shapiro-Wilk test were employed to analyze data. According to the results, the attitude toward a proposed system was found to be the major determinant of adoption intention (β = .672, p < .001); at the same time, the core model accounted for 67.2% of explained variance. Two additional predictors proved to be significant, cost acceptance (ΔR² = .060, p = .002) and infrastructure concerns (ΔR² = .022, p = .072). Against previous theoretical predictions formed according to the post-Soviet urban infrastructure literature, no statistically significant differences between residents of apartment buildings and those who live in private houses were found on any core TPB construct, suggesting that the architectural legacy of communal waste systems does not translate into differentiated consumer attitudes. The paper concludes that a city-wide introduction of the system is recommended with special attention paid to fair communication, tariff calibration within the 5–15 AZN range, and transparency of the process. The study contributes an empirically grounded analysis of PAYT acceptance in a transition economy context underrepresented in the existing literature
Keywords: Pay-As-You-Throw; food waste; Theory of Planned Behavior; consumer acceptance; Baku; post-Soviet urban infrastructure